2012
DOI: 10.1007/s10867-012-9270-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragmentation by gamma radiation and electron beams using atomic force microscopy

Abstract: Double-stranded pBS plasmid DNA was irradiated with gamma rays at doses ranging from 1 to 12 kGy and electron beams from 1 to 10 kGy. Fragment-size distributions were determined by direct visualization, using atomic force microscopy with nanometer-resolution operating in non-tapping mode, combined with an improved methodology. The fragment distributions from irradiation with gamma rays revealed discrete-like patterns at all doses, suggesting that these patterns are modulated by the base pair composition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Other investigators have subsequently applied AFM for further studies of radiation induced DNA damage (Murakami et al, 2000 ; Brons et al, 2004 ; Psonka et al, 2005 ; Brezeanu et al, 2007 ; Elsässer et al, 2008 ; Ke et al, 2008 ; Gudowska-Nowak et al, 2009 ; Lee et al, 2009 ; González et al, 2012 ). Of particular relevance to measurement of short DNA fragments by high-LET radiations, Psonka-Antonczyk et al ( 2009 ) investigated DNA breakage by Ni ions and observed a reduced average DNA fragment length after 340-Gy irradiation when compared to X-ray irradiations.…”
Section: Afm Investigation Of Radiation-induced Plasmid Dna Fragmentamentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have subsequently applied AFM for further studies of radiation induced DNA damage (Murakami et al, 2000 ; Brons et al, 2004 ; Psonka et al, 2005 ; Brezeanu et al, 2007 ; Elsässer et al, 2008 ; Ke et al, 2008 ; Gudowska-Nowak et al, 2009 ; Lee et al, 2009 ; González et al, 2012 ). Of particular relevance to measurement of short DNA fragments by high-LET radiations, Psonka-Antonczyk et al ( 2009 ) investigated DNA breakage by Ni ions and observed a reduced average DNA fragment length after 340-Gy irradiation when compared to X-ray irradiations.…”
Section: Afm Investigation Of Radiation-induced Plasmid Dna Fragmentamentioning
confidence: 99%
“…Such high purity DNA is obtained using plasmid DNA; therefore, measurements of chromosomal DNA fragments generated in cells will require the development of DNA techniques suitable for AFM imaging. (3) To generate enough short DNA fragments to permit sampling in a reasonable number of AFM images, investigators have used high radiation doses in the kGy range to irradiate and break the DNA molecules, raising the obvious question of biological relevance, where typical therapeutic radiation doses are only a few Gy (Pang et al, 1998 ; González et al, 2012 ).…”
Section: Afm Investigation Of Radiation-induced Plasmid Dna Fragmentamentioning
confidence: 99%
“…Moreover, the atomic force microscopy (AFM) technique has been used to monitor changes in the different substrates produced by photothermal processes, such as DNA fragmentation [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fraction of undamaged plasmids after irradiation with different electron doses was quantitatively also analyzed by means of intermittent contact AFM, which has developed into a standard technique for imaging susceptible biomolecules 14 with nanometer resolution. In particular, AFM has been used for structural analysis of supercoiled, open circular and linearized plasmid DNA as well as for analysis of contour lengths of linear DNA, which was fragmented by radiation 15 18 .…”
Section: Resultsmentioning
confidence: 99%
“…The large number of short fragments is the result of densely localized ionization events in the proximity of the DNA. Hence, it is widely accepted that this is leading to destabilising the secondary structure of DNA 14 18 . Depending on the dose and the type of radiation, the effect of DNA lesions are ranging from cross-links, base releases and combination of single strand-breaks, double strand-breaks to clustered double-strand breaks 21 23 .…”
Section: Discussionmentioning
confidence: 99%